Mental illness in people who kill strangers: longitudinal study and national clinical survey. Issue 7442 (25th March 2004) - Shaw, Jenny; Amos, Tim; Hunt, Isabelle M; Flynn, Sandra; Turnbull, Pauline; Kapur, Navneet; Appleby, Louis
Abstract: Objectives To establish changes over time in the frequency of homicides committed by strangers, and to describe the personal and clinical characteristics of perpetrators of stranger homicides. Design Longitudinal study and national clinical survey. Participants People convicted of homicide in England and Wales between 1996 and 1999 and whether the victim was known to the perpetrator. Setting England and Wales. Main outcome measure Characteristics of perpetrators of homicides according to whether victims were strangers or not. Results Stranger homicides increased between 1967 and 1997, both in number and as a proportion of all homicides. No increase was found, however, in the number of perpetrators placed under a hospital order after homicide, whether all homicides or stranger homicides only. 358 of 1594 (22%) homicides were stranger homicides. In these cases the perpetrator was more likely to be male and young. The method of killing was more likely to be by hitting, kicking, or pushing (36% (130 of 358) for victims who were strangers to the perpetrator compared with 14% (145 of 1074) for victims who were known). Perpetrators were less likely to have a history of mental disorder (34%, n = 80 ν 50%, n = 142), a history of contact with mental health services (16%, 37 of 234 ν 24%, 200 of 824), and psychiatric symptoms at the time of the offence (6%, n = 14 ν 18%, n = 143). They were more likely to have a history of drug misuse (47%, n = 93 ν 37%, n = 272); alcohol (56%, n = 94 ν 41%, n = 285) or drugs (24% n = 44 ν 12%, n = 86) were more likely to have contributed to the offence. Conclusions Stranger homicides have increased, but the increase is not the result of homicides by mentally ill people and therefore the "care in the community" policy. Stranger homicides are more likely to be related to alcohol or drug misuse by young men.